Warfarin-related outcomes in patients with antiphospholipid antibody syndrome managed in an anticoagulation clinic - Wittkowsky, Ann K.; Downing, Jennifer; Blackburn, Juan; Nutescu, Edith (Thrombosis and Haemostasis, 2006)
Patients with antiphospholipid antibody syndrome (APA) are at elevated risk of venous and arterial thromboembolic complications. Oral anticoagulation with warfarin is recommended for secondary prevention of thromboembolism, but warfarin-related outcomes have not been systematically investigated when warfarin therapy is managed by a dedicated anticoagulation clinic.The objectives of the study were to evaluate warfarin-related monitoring outcomes, clinical endpoints and the use of healthcare resources as a result of warfarin-related complications in patients with APA compared to a group of patients without APA, all of whom were managed in an anticoagulation clinic setting. A retrospective observational cohort design was used to investigate patients with and without APA, all of whom had a history of venous or arterial thromboembolism, and were matched for age, gender and indication for oral anticoagulation. Thirty-six APA patients taking warfarin were compared to a matched cohort of 36 patients without APA. Monitoring outcomes (time in therapeutic range, clinic visits per year, frequency of warfarin dosing adjustments, reasons for out-of-range INRs) were similar between groups, as was the frequency of major bleeding complications (3.2%/pt-yr vs. 3.1%/pt-yr). However, recurrent thromboembolic events (9.6%/pt-yr vs 0) occurred more frequently in APA patients. APA patients required more emergency room visits (6.4%/pt-yr vs. 1.6%/pt-yr) and hospital admissions (14.4%/pt-yr vs.3.0%/pt-yr) to manage complications of warfarin therapy. In conclusion, despite similar monitoring outcomes obtained in a dedicated anticoagulation clinic setting, adverse clinical outcomes are significantly more frequent in patients with APA syndrome than in those without APA, and require more frequent use of healthcare resources.
Keywords: Warfarin; antiphospholipid antibody syndrome; thrombosis; anticoagulation clinic